Legal Politics of Decentralization and the Challenges of Local Democracy in Indonesia - Amirullah; Ahsanul haq; Muh. Sabir; Mutiatun ni’ma; Yahya; Rahmat (www.amertainstitute.com, 2026)
Decentralization constitutes a central legal-political strategy in Indonesia’s constitutional framework, aimed at redistributing governmental authority from the central government to regional governments in order to enhance public service delivery, governance effectiveness, and the quality of local democracy. As a unitary state, Indonesia adopts decentralization not merely as an administrative arrangement but as a constitutional mandate embedded in Article 18 of the 1945 Constitution, further operationalized through various laws on regional governance. This study examines the legal politics of decentralization in Indonesia and analyzes the challenges it poses to the realization of substantive local democracy. Employing a normative juridical research method, this study uses statutory and conceptual approaches to analyze constitutional provisions, laws on regional government, and relevant legal doctrines. The findings indicate that while decentralization has opened broader opportunities for local autonomy, political participation, and policy innovation, its implementation has also generated significant democratic challenges at the local level. These challenges include the consolidation of local oligarchies, the persistence of political dynasties, corruption, weak institutional capacity, and limited meaningful public participation. In many regions, decentralization has resulted in a shift of power from central elites to local elites rather than genuine empowerment of citizens. This condition reveals a normative–empirical gap between the objectives of decentralization and the realities of local democratic practices. The study argues that the effectiveness of decentralization in strengthening local democracy depends on consistent legal-political orientation, strengthened oversight mechanisms, institutional capacity building at the regional level, and the enhancement of civic participation and political literacy. Without these measures, decentralization risks functioning merely as an administrative transfer of authority rather than as an instrument for deepening democracy and achieving social justice.